Radiology Interest Groups: A Recipe for Success. Issue 3 (August 2021) - Dobson, Jessica L.; Fenwick, Andrew; Linehan, Victoria; Hartery, Angus
Objectives: Radiology Interest Groups (RIGs) are valuable for medical students and the radiology profession. The purpose of this study is to identify key components of a successful RIG and to discuss how to optimize available resources to increase student engagement in radiology. Methods: Anonymous feedback forms (n = 478) completed by preclinical medical students attending 20 RIG events between September 2016 and May 2019 were analyzed. A five-point Likert-type scale was used to determine event effectiveness, and important themes reflecting student perspectives were identified using thematic analysis of freeform comments. Results: Based on Likert feedback, 75% to 78% of students had a positive experience of RIG events and believed sessions were relevant to their studies. 31% to 42% of students believed these events increased their interest or insight into radiology and influenced their career choice. Four representative themes were identified by qualitative analysis of written feedback: engagement, professional development, mentorship, and suggestions for improvement. These themes provided insight into student perspectives of our RIG, and, along with experience from the RIG organizers, the authors present elements perceived to have contributed to these positive results. Conclusion: Thematic analysis of feedback reveals that students consider interactive events, contribution to professional development, and the opportunity for mentorship valuable elements of a RIG. From the perspective of the organizing committee, we embody these aspects through careful planning, innovative events, and consistent debriefing. In this way, our RIG promotes the future of the radiology profession and serves as a practical model for other similar organizations.